2015
DOI: 10.1115/1.4028494
|View full text |Cite
|
Sign up to set email alerts
|

Origins and Structure of Spike-Type Rotating Stall

Abstract: In this paper, we describe the structures that produce a spike-type route to rotating stall and explain the physical mechanism for their formation. The descriptions and explanations are based on numerical simulations, complemented and corroborated by experiments. It is found that spikes are caused by a separation at the leading edge due to high incidence. The separation gives rise to shedding of vorticity from the leading edge and the consequent formation of vortices that span between the suction surface and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(98 citation statements)
references
References 20 publications
(32 reference statements)
7
83
2
Order By: Relevance
“…However, in contrast to the findings of Pullan et al (2015) [20], the localised disturbance does not evolve into a stall cell after a few rotor revolutions. In the presented case, discrete vortex structures remain unchanged when the through-flow is constant-they represent indeed a kind of flow non-uniformity but they are not responsible for flow separation or part span stall.…”
Section: Prestall Propagating Disturbances; Numerical Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…However, in contrast to the findings of Pullan et al (2015) [20], the localised disturbance does not evolve into a stall cell after a few rotor revolutions. In the presented case, discrete vortex structures remain unchanged when the through-flow is constant-they represent indeed a kind of flow non-uniformity but they are not responsible for flow separation or part span stall.…”
Section: Prestall Propagating Disturbances; Numerical Resultscontrasting
confidence: 98%
“…Rotation of the vortex tube is indicated by white and black arrows. In general, the coherent flow topology strongly resembles a classical spike formation known from spike stall inception mechanisms [20]. A similar flow topology was also addressed by Inoue et al (2001) [21] who described the occurrence of short length-scale stall cells when the compressor is operating in a mild stall condition.…”
Section: Prestall Propagating Disturbances; Numerical Resultsmentioning
confidence: 65%
“…When impinging on the leading edge, the vortex causes significant variations in Once the described pattern has established, it is self-sustaining and travels around the circumference, as depicted in Figure 12. This agrees with the system described by Inoue et al (2000), and was recently documented by Pullan et al (2015) for a subsonic compressor. The measurements cannot be used to determine whether the tip leakage vortex is part of the shed radial vortices or remains attached to the blade.…”
Section: Resultssupporting
confidence: 91%
“…The vortices may be the initiator of a spike (Camp and Day, 1998), i.e., a short-length scale disturbance with high circumferential velocity (>70% rotor speed depending on the setup), developing into a rotating stall cell. The shape of the structures is described as a tornado-like vortex, with one end attached to the rotor blade and the other bound to the casing and traveling towards the adjacent blade (Inoue et al, 2000;Pullan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, much effort has been made to reveal the nature of TLF and researchers have made noteworthy progress on the potential relation between the stall inception and the unsteady phenomena in the tip region [3][4][5][6][7][8][9][10][11][12]. It has been found that the TLF could become unsteady at high loading operating conditions and the tip leakage vortex plays an important role in the stall inception process.…”
Section: Introductionmentioning
confidence: 99%